RANCANG BANGUN WEBSITE SISTEM INFORMASI SUPPLY CHAIN MANAJEMEN PADA BISNIS PERGURUAN TINGGI - Ana Rohmah zaidah; Achmad Fauzi Saputra; Yusuf Amrozi (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Indonesia as a developing country has made an agreement to take part in the process of reducing the impact of global warming and environmental issues, including waste problems. With the Green Campus program, the government supports all academics to care about this process. This is realized through the integration of science such as Supply Chain Management with information systems that focus on university business processes, one of which is a waste bank, which will later designate a university waste bank information system. This design uses the waterfall method with a series of analyses, design, implementation, testing and maintenance. It is hoped that this research will be able to provide suggestions for the design process for supply chain management in higher education businesses.